A cucurbit[5]uril analogue from dimethylpropanediurea–formaldehyde condensation1. Issue 14 (18th February 2015) - Jiang, Xiaoqing; Yao, Xuyang; Huang, Xinghua; Wang, Qiaochun; Tian, He
<x xml:space="preserve">Abstract</x> A new cucurbit[5]uril-like macrocycle has been synthesized and shows good solubility in water and organic solvents.